Development of Brazilian prototypes for short-term psychotherapies - Fernanda Barcellos Serralta; John Stuart Ablon (Trends in Psychiatry and Psychotherapy)
Abstract Introduction: The Psychotherapy Process Q-Set (PQS) prototype method is used to measure the extent to which ideal processes of different psychotherapies are present in real cases, allowing researchers to examine how adherence to these models relates to or predicts change. Results from studies of short-term psychotherapies suggest that the original psychodynamic prototype is more suitable for studying psychoanalysis and long-term psychodynamic psychotherapy than its time-limited counterparts. Furthermore, culture probably influences how therapies are typically conducted in a given country. Therefore, it seems appropriate to develop Brazilian prototypes on which to base studies of short-term psychodynamic and cognitive-behavioral processes in this country. Objective: To develop prototypes for studying processes of short-term psychotherapies and to examine the degree of adherence of two real psychotherapy cases to these models. Methods: Expert clinicians used the PQS to rate a hypothetical ideal session of either short-term psychodynamic psychotherapy (STPP) or cognitive-behavioral therapy (CBT). Ratings were submitted to Q-type factor analysis to confirm the two groups. Regressive factor scores were rank ordered to describe the prototypes. These ideal models were correlated with ratings of actual therapy processes in two complete psychotherapy cases, one STPP and the other CBT. Results: Agreement levels between expert ratings were high and the two ideal models were confirmed. As expected, the PQS ratings for actual STPP and CBT cases had significant correlations with their respective ideal models, but the STPP case also adhered to the CBT prototype. Conclusion: Overall, the findings reveal the adequacy of the prototypes for time-limited therapies, providing initial support of their validity.